Lateral, Vertical, and Temporal Variability of Seawater Carbonate Chemistry at Hog Reef, Bermuda - Pezner, Ariel K.; Courtney, Travis A.; Page, Heather N.; Giddings, Sarah N.; Beatty, Cory M.; DeGrandpre, Michael D.; Andersson, Andreas J. (Frontiers in Marine Science, 2021)
Spatial and temporal carbonate chemistry variability on coral reefs is influenced by a combination of seawater hydrodynamics, geomorphology, and biogeochemical processes, though their relative influence varies by site. It is often assumed that the water column above most reefs is well-mixed with small to no gradients outside of the benthic boundary layer. However, few studies to date have explored the processes and properties controlling these multi-dimensional gradients. Here, we investigated the lateral, vertical, and temporal variability of seawater carbonate chemistry on a Bermudan rim reef using a combination of spatial seawater chemistry surveys and autonomous in situ sensors. Instruments were deployed at Hog Reef measuring current flow, seawater temperature, salinity, pHT, pCO2, dissolved oxygen (DO), and total alkalinity (TA) on the benthos, and temperature, salinity, DO, and pCO2 at the surface. Water samples from spatial surveys were collected from surface and bottom depths at 13 stations covering ∼3 km2 across 4 days. High frequency temporal variability in carbonate chemistry was driven by a combination of diel light and mixed semi-diurnal tidal cycles on the reef. Daytime gradients in DO between the surface and the benthos suggested significant water column production contributing to distinct diel trends in pHT, pCO2, and DO, but not TA. We hypothesize these differences reflect the differential effect of biogeochemical processes important in both the water column and benthos (organic carbon production/respiration) vs. processes mainly occurring on the benthos (calcium carbonate production/dissolution). Locally at Hog Reef, the relative magnitude of the diel variability of organic carbon production/respiration was 1.4–4.6 times larger than that of calcium carbonate production/dissolution, though estimates of net organic carbon production and calcification based on inshore-offshore chemical gradients revealed net heterotrophy (−118 ± 51 mmol m–2 day–1) and net calcification (150 ± 37 mmol CaCO3 m–2 day–1). These results reflect the important roles of time and space in assessing reef biogeochemical processes. The spatial variability in carbonate chemistry parameters was larger laterally than vertically and was generally observed in conjunction with depth gradients, but varied between sampling events, depending on time of day and modifications due to current flow.